LESI NERVUS OKULOMOTOR INVOLVED PUPIL ET CAUSA ANEURISMA PADA PASIEN DENGAN STROKE SUBARACHNOID HEMORRHAGIC DAN SYSTEMIC LUPUS ERITHEMATOSUS - I Ketut Aryawan; Anak Agung Mas Putrawati Triningrat; Made Paramita Wijayanti; Ida Ayu Sri Indrayani; Pande Ketut Kurniari (Callosum Neurology, 2021)
Introduction: Oculomotor nerve palsy is an pathological condition caused by microvascular injury, head injury, compression due to neoplasm or aneurysm, and also oculomotor nerve palsy can be caused by autoimmune prosses. Peripheral neuropathy is one of the clinical manifestations in patient with SLE, Oculomotor nerve palsy is one type of cranial neuropathy seen with SLE patient. Patient with SLE have a higher risk of serebrovascular event than general population. Case Illustration: Female 34 years old complained drop of the eyelid on the left eye and double vision when see with both eyes since 1 mounth before examination. Patient with history of headace and diagnosed with SLE since 2006 with regular treatment. From the examination, pupil anisocor, on the right eye pupil was 3 mm in diameter with positif direct and indirect reflex. On the left eye pupil was 6 mm with negative direct and indirect reflex. Extraocular movement on the left eye was limited except abduction movement.  CT-Scan examination shows bilateral subarachnoid hemorrhage and from CT-Angiography shows dilatation of the left siphon carotid artery. Patient was diagnosed with oculomotor nerve palsy involving pupil caused by aneurysm with SAH and SLE. Discussion: Oculomotor nerve palsy mostly caused by aneurysm compression in posterior communicating artery (PCoA) and internal carotid artery (ICA). Cerebrovascular imaging, MRA and CTAngiography, can showing the aneurysm and its location. Risk of cerebrovascular event increased in patient with SLE than general population. Management patient with oculomotor nerve palsy with SLE nowadays is with pulse dose corticosteroid. Conclusion: SLE with oculomotor nerve palsy will increase risk of cerebrovascular event. Key Words : Oulomotor Nerve Palsy, Subarachnoid Hemorrhage, Systemic Lupus Erithematosus